The Implications of a Ruling that is Insufficiently Motivated in Assesing Land Ownership by Communities on HGU Land - Sutjiadi, Andreas; Rahayu, Mella Ismelina Farma (Jurnal Daulat Hukum, 2025)
This study is motivated by the gap between the judicial ideal, which obliges judges to provide adequate legal reasoning (motiveringsplicht), and the reality in appellate courts that often produce onvoldoende gemotiveerd (insufficiently reasoned) decisions. Weak judicial reasoning not only increases the risk of annulment by the Supreme Court but also worsens the legal standing of local communities in land disputes over Hak Guna Usaha (HGU). The research gap lies in the lack of studies linking appellate court decisions to the legal status of community landholders on HGU plots. This research employs a normative juridical approach with doctrinal analysis supported by secondary data from court rulings and agrarian law literature. The findings reveal that onvoldoende gemotiveerd decisions undermine the legitimacy of district courts, prolong agrarian disputes, and intensify the dualism between formal law and social reality. This study highlights the urgency of reforming judicial reasoning so that the layered court system can deliver substantive justice while ensuring legal certainty for affected communities.